Upregulation of the Glutaminase II Pathway Contributes to Glutamate Production upon Glutaminase 1 Inhibition in Pancreatic Cancer. Issue 21 (1st August 2019) - Udupa, Sunag; Nguyen, Stephanie; Hoang, Giang; Nguyen, Tu; Quinones, Addison; Pham, Khoa; Asaka, Ryoichi; Nguyen, Kiet; Zhang, Cissy; Elgogary, Amira; Jung, Jin G.; Xu, Qingguo; et al.
Abstract: The targeting of glutamine metabolism specifically via pharmacological inhibition of glutaminase 1 (GLS1) has been translated into clinical trials as a novel therapy for several cancers. The results, though encouraging, show room for improvement in terms of tumor reduction. In this study, the glutaminase II pathway is found to be upregulated for glutamate production upon GLS1 inhibition in pancreatic tumors. Moreover, genetic suppression of glutamine transaminase K (GTK), a key enzyme of the glutaminase II pathway, leads to the complete inhibition of pancreatic tumorigenesis in vivo unveiling GTK as a new metabolic target for cancer therapy. These results suggest that current trials using GLS1 inhibition as a therapeutic approach targeting glutamine metabolism in cancer should take into account the upregulation of other metabolic pathways that can lead to glutamate production; one such pathway is the glutaminase II pathway via GTK.